Unitary and Non-Unitary Precoders for a Limited Feedback Precoded OSTBC System - Wang, Haiquan; Li, Yabo; Xia, Xiang-Gen; Liu, Shunlan (IEEE transactions on vehicular technology, 2013)
In this paper, a multiple-input-multiple-output (MIMO) system with finite-bit feedback first proposed by Love-Heath is considered, where a transmitted signal consists of a precode followed by an orthogonal space-time block code (OSTBC), such as Alamouti code. A new design criterion and a corresponding design method of precoders are proposed. Simulations show that the precoders obtained by our proposed criterion and method perform better than the existing ones. Furthermore, since our proposed precoders have a layered structure, their designs can be implemented in the simplest Grassmannian manifold. Moreover, a fast encoding algorithm can be applied, which can greatly reduce the complexity of codeword selection. In this paper, we also propose non-unitary precoders and their design criterion and method based on the performance analysis and the special property of an OSTBC. Interestingly, non-unitary precoders can significantly improve performance over unitary precoders.